AN IMPROVED NEW MODEL FOR TOURIST FLOW BETWEEN THE DIVIDED TWO KOREAS - YOUNGSUN SHIN (ASEAN Journal on Hospitality and Tourism, 2006)
On April 13-15, 2000 South and North Korean leaders gathered in Pyongyang for a meeting of peace ending over fifty years of hostilities. According to this meeting, South and North Korea were believed to be among the economies most directly affected by the world peace process. This had a large effect on both countries in many aspects, socially, politically and economically. One of the sectors, which may gain immediate benefits, is tourism even though the study of the relationship between tourism and peace is relatively new. This study investigates of peace tourism trends between politically divided South and North Korea. It examines tourism as past, present and future activities in influencing reconciliation between the two purpils and governments and discusses the current state of affairs of this two countries and tourism between South and North Korea.